Ammonite-benthic Foraminifera turnovers across the Lower-Middle Jurassic transition in the Lusitanian Basin (Portugal) - Henriques, Maria Helena Paiva (2013)
This paper describes and characterises the co-occurrence of ammonite and benthic foraminiferal assemblages across the São Gião outcrop (Central Portugal), a reference section for the Lower-Middle Jurassic boundary in the Lusitanian Basin. The upper Toarcian-lower Aalenian marls and marly-limestones in this section provide a precise and detailed ammonite-based biostratigraphic zonation, with a mixed assemblage of northwest European and Mediterranean faunal elements, associated with benthic foraminifera assemblages with northern hemisphere affinities, both correlatable with the Aalenian GSSP at the Fuentelsaz section (Iberian Cordillera, Spain). A total of 447 well-preserved ammonite specimens and 13.116 foraminifera have been studied; no evidence was detected of any taphonomic processes that could have changed the original assemblages. From a biostratigraphic point of view, the ammonite record has enabled four biostratigraphic units to be recognised (the Mactra and Aalensis subzones of the Aalensis Biozone in the upper Toarcian, and the Opalinum and Comptum subzones of the Opalinum Biozone in the lower Aalenian). With regard to the benthic foraminifera, the taxa identified have enabled the Astacolus dorbignyi Zone and 11 bioevents to be identified, most of which representing local biostratigraphic proxies. However, the increase in the relative abundance of Lenticulina exgaleata Dieni from the upper part of the Opalinum Subzone to the lower part of the Comptum Subzone has a regional value. The constant and continuous ammonite record of northwest European taxa, together with typical Mediterranean taxa – namely Grammoceratinae – throughout the section, the high relative abundance of Miliolina representatives – generally interpreted as foraminifers typical of shallow waters – and the absence of foraminiferal forms typical of cool waters, do not support the inference of cool seawater temperatures attributed to the Early Aalenian, or the global character of the “Comptum cooling event”, at least with reference to the Lusitanian Basin.